Series Solutions to Second Order Linear Differential Equations We have fully investigated solving second order linear differential equations with constant coefficients.  Now we will explore how to find solutions to second order linear differential equations whose coefficients are not necessarily constant.  Let         P(x)y'' + Q(x)y' + R(x)y  =  g(x) Be a second order differential equation with P, Q, R, and g all continuous.  Then x0 is a singular point if P(x0)  =  0, but Q and R do not both vanish at x0.  Otherwise we say that x0 is an ordinary point.  For now, we will investigate only ordinary points.   Example Find a solution to          y'' + xy' + y  =  0    y(0)  =  0    y'(0)  =  1   Solution Since the differential equation has non-constant coefficients, we cannot assume that a solution is in the form y  =  ert.  Instead, we use the fact that the second order linear differential equation must have a unique solution.  We can express this unique solution as a power series If we can determine the an for all n, then we know the solution.  Fortunately, we can easily take derivatives Now we plug these into the original differential equation We can multiply the x into the second term to get We would like to combine like terms, but there are two problems.  The first is the powers of x do not match and the second is that the summations begin in differently.  We will first deal with the powers of x.  We shift the index of the first summation by letting          u  =  n - 2        n  =  u + 2 We arrive at Since u is a dummy variable, we can call it n instead to get Next we deal with the second issue.  The second summation begins at 1 while the first and third begin at 0.  We deal with this by pulling out the 0th term.  We plug in 0 into the first and third series to get         (0 + 2)(0 + 1)a0+2x0  =  2a2 and         a0x0  =  a0  We can write the series as The initial conditions give us that          a0  =  0        and        a1  =  1 Now we equate coefficients.  The terms in the series begin with the first power of x, hence the constant term gives us         2a2 + a0  =  0 Since a0  =  0, so is a2.  Now the coefficient in front of xn is zero for all n.  We have         (n + 2)(n + 1)an+2 + (n + 1)an  =  0   Solving for an+2 gives                        -an         an+2  =                                        n+2 We immediately see that          an  =  0 for n even.  Now compute the odd an                                       -1                      1                          -1         a1  =  1        a3  =                 a5  =                    a7  =                                                       3                     3.5                        3.5.7 In general                                  (-1)n                            2n(n!)(-1)n            a2n+1  =                                 =                                                                 3.5.7.....(2n+1)                  (2n + 1)! The final solution is This cannot be written in terms of elementary functions, however a computer can graph or calculate a value with as many decimal places as needed.   Example Find the the first three nonzero terms of two linearly independent solutions to           xy'' + 2y  =  0          Solution Notice that 0 is a singular point of this differential equation.  We will not be able to find a solution in the form Sanyn, since the solution will not be differentiable at zero.  Alternatively, we find a solution in the form This is the power series centered about x  =  1, which is not a singular point.  Now take derivatives Plugging into the differential equation gives Writing          x  =  (x - 1) + 1 and multiplying through gives Let u  =  n - 2 in the first summation, u  =  n - 2 in the second and then changing the index variable back to n gives Now plugging in n  =  0 into the second and third series we get Now we can equate coefficients to find         2a2 + 2a0  =  0         (n + 1)nan+1 + (n + 2)(n + 1)an+2 + 2an  =  0 The first equation says that          a2  =  -a0  The recursion relationship says                         -(n + 1)nan+1 - 2an         an+2  =                                                                                (n + 2)(n + 1)    We want to find two linearly independent solutions.  To do this, we can choose the first two terms of the series.  The easiest choices are          a0  =  0    a1  =  1            and            a0  =  1    a1  =  0 Plugging the first pair, we get         a0  =  0    a1  =  1    a2  =  0    a3  =  [-2(0) - 2(1)]/6  =  -1/3         a4  =  [-2(3)(-1/3) - 2(0)]/12  =  1/6 Plugging in the second pair, we get         a0  =  1    a1  =  0    a2  =  -1    a3  =  [-2(-1) - 2(0)]/6  =  1/3 We can write         y1  =  (x - 1) - 1/3 (x - 1)3 + 1/6 (x - 1)4 + ...         y2  =  1 - (x - 1)2 + 1/3 (x - 1)3 + ... Back to the Differential Equations Home Page